The Phrygian ethnos - Kempiński, Andrzej M. (Balcanica Posnaniensia. Acta et studia, 1990)
The article addresses the problem of the definition and scope of the concept of “Phrygians” and the reconstruction of the ethnic structure of this population, whose interpretation in historiography remains ambiguous and contradictory. The problem is significant due to the lack of coherent studies and the dispersion of data used selectively by various disciplines. The aim of the work is to determine the actual meaning of the term and to define the relationships between the various ethnic names attributed to this group. The author applies analysis of ancient sources, etymology, and a comparative linguistic and historical method. The most important results indicate that the term “Phrygians” was used inconsistently and included various ethnic groups, such as the Brygians and Mygdonians, which in fact constituted elements of one larger ethnic complex. The analysis of variants of the ethnonym (e.g., Brygians/Phrygians) demonstrates their common Indo-European origin and transformations resulting from linguistic differences and cultural contacts. The author also demonstrates that migrations of this population from the Balkans to Asia Minor and their presence in different regions explain the diversity of names and traditions. The conclusion of the work is the thesis of the existence of a coherent Phrygian ethnos, whose nomenclatural diversity resulted from linguistic and regional conditions rather than actual ethnic fragmentation.